2014
DOI: 10.1371/journal.pone.0088067
|View full text |Cite
|
Sign up to set email alerts
|

Indian-Ink Perfusion Based Method for Reconstructing Continuous Vascular Networks in Whole Mouse Brain

Abstract: The topology of the cerebral vasculature, which is the energy transport corridor of the brain, can be used to study cerebral circulatory pathways. Limited by the restrictions of the vascular markers and imaging methods, studies on cerebral vascular structure now mainly focus on either observation of the macro vessels in a whole brain or imaging of the micro vessels in a small region. Simultaneous vascular studies of arteries, veins and capillaries have not been achieved in the whole brain of mammals. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 27 publications
1
47
0
Order By: Relevance
“…In contrast to the brain's electrical circuit diagram, which is far from complete in any mammalian model organism, recent breakthroughs in imaging and sectioning technology have resulted in high-resolution capillary-level reconstructions of the rodent brain angiome Mayerich et al, 2011;Pathak et al, 2011;Tsai et al, 2009;Xue et al, 2014). Tracing blood vessels is (A) At the microscale level, serial blockface scanning electron microscopy has been used to reconstruct a volume of rodent brain tissue and manually trace a segment of spiny dendrite (shown in red) to visualize synaptic connections.…”
Section: The Brain's Connectome Assessed By Multiple Measures and Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the brain's electrical circuit diagram, which is far from complete in any mammalian model organism, recent breakthroughs in imaging and sectioning technology have resulted in high-resolution capillary-level reconstructions of the rodent brain angiome Mayerich et al, 2011;Pathak et al, 2011;Tsai et al, 2009;Xue et al, 2014). Tracing blood vessels is (A) At the microscale level, serial blockface scanning electron microscopy has been used to reconstruct a volume of rodent brain tissue and manually trace a segment of spiny dendrite (shown in red) to visualize synaptic connections.…”
Section: The Brain's Connectome Assessed By Multiple Measures and Scalesmentioning
confidence: 99%
“…Optimization of histological and sectioning techniques in combination with classic methods such as India ink perfusion has resulted in remarkably complete brain-wide capillary-level data sets for mice (Mayerich et al, 2011;Xue et al, 2014). Such data may be used to predict local vulnerability to vascular disruptions, but insight from the data with respect to stroke is still in progress.…”
Section: The Brain's Connectome Assessed By Multiple Measures and Scalesmentioning
confidence: 99%
“…[1][2][3] . Although structural and molecular analyses of cerebral vasculature are promising for providing fundamental insights into cerebral circulation and cerebrovascular diseases, which are major causes of death and disability 4 , few studies have captured detailed structural information of molecularly identified vascular networks due to technical limitations (Supplementary Tables 1 and 2) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] .…”
mentioning
confidence: 99%
“…After the loss of any reflex, before the euthanasia by the barbiturate overdose administered intraperitoneally (Pentobarbital solution, Sigma-Aldrich, 300mg/kg), the animals were intracardiacally perfused according to a common protocol [4]. The procedure was performed in four stages: heparinized saline (150-180 ml), 10% formalin (150 ml), air (ten minutes of air insufflation through the same route of fluids and, eventually, undiluted Indian-ink (100 ml), this last used in accordance with the modified protocol by Xue et al [64]. The unusual step of injecting air into the circulating system after the vessel fixation was adopted to empty the vascular system before the ink injection.…”
Section: Perfusion Methodsmentioning
confidence: 99%